IMPLEMENTASI SISTEM KEAMANAN JARINGAN BERBASIS WEB: LOGGING, DETEKSI ANOMALI DAN PEMBLOKIRAN OTOMATIS - Situmorang, Romatua; Kiswanto, Dedy; Khoiriah, Najwatul; Harahap, Fatima Asro (Universitas Lampung, 2026)
This research aims to implement a web-based network security system that integrates logging, anomaly detection, and automatic blocking capabilities against suspicious activities. The significance of this topic is underpinned by the increasing cyber threats, such as brute force and high request rate attacks, which directly jeopardize system availability. The system is designed using Python Flask and PostgreSQL as the server architecture, employing a Rule-Based detection method to identify specific attack patterns. Testing with Kali Linux simulations proved that the system was 100% effective in successfully providing alerts and effectively blocking attacker IPs. The successful implementation of this internal IPS (Intrusion Prevention System) is validated by the server's denial of access and the display of the message